Variability of articulator positions and formants across nine English vowels. (May 2018) - Whalen, D.H.; Chen, Wei-Rong; Tiede, Mark K.; Nam, Hosung
Highlights: Variability in two domains, articulatory and acoustic, was compared for 9 English vowels produced by 32 speakers in the X-ray microbeam database (XRMB; Westbury, 1994). Individual tokens were closer to the acoustic median than to the articulatory only about half the time, indicating balance of the two factors for each speaker (range: 40–60%). Speakers who were relatively variable on one vowel were relatively variable on the other vowels as well. Acoustic and articulatory variability were positively correlated. Abstract: Speech, though communicative, is quite variable both in articulation and acoustics, and it has often been claimed that articulation is more variable. Here we compared variability in articulation and acoustics for 32 speakers in the X-ray microbeam database (XRMB; Westbury, 1994). Variability in tongue, lip and jaw positions for nine English vowels (/u, ʊ, æ, ɑ, ʌ, ɔ, ɛ, ɪ, i/) was compared to that of the corresponding formant values. The domains were made comparable by creating three-dimensional spaces for each: the first three principal components from an analysis of a 14-dimensional space for articulation, and an F1xF2xF3 space for acoustics. More variability occurred in the articulation than the acoustics for half of the speakers, while the reverse was true for the other half. Individual tokens were further from the articulatory median than the acoustic median for 40–60% of tokens across speakers. A separate analysis of three non-low front vowels (/ɛ, ɪ, i/, for which the XRMB system provides the most direct articulatory evidence) did not differ from the omnibus analysis. Speakers tended to be either more or less variable consistently across vowels. Across speakers, there was a positive correlation between articulatory and acoustic variability, both for all vowels and for just the three non-low front vowels. Although the XRMB is an incomplete representation of articulation, it nonetheless provides data for direct comparisons between articulatory and acoustic variability that have not been reported previously. The results indicate that articulation is not more variable than acoustics, that speakers had relatively consistent variability across vowels, and that articulatory and acoustic variability were related for the vowels themselves.